2001
DOI: 10.1007/s004670000495
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction but not cystic change is ameliorated by neonatal epidermal growth factor in bpk mice

Abstract: BALB/c mice homozygous for the bpk gene exhibit a form of autosomal recessive (AR) polycystic kidney disease (PKD) with massive collecting duct cysts, common bile duct dilation and chaotic intrahepatic bile ducts/portal triads. The combined renal and biliary pathology mimics much of the pathology seen in human ARPKD. Murine models of ARPKD generally have a reduced renal expression of epidermal growth factor (EGF) and an increased expression of EGF receptors (EGF-R). However, the role that EGF and EGF-R play in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The timing of overexpression during the course of development may also impact the effect of growth factor on disease progression. In the bpk mouse, administration of exogenous EGF before 9 d of age improved renal function but not cystic kidney appearance, whereas, when treatment was continued beyond 9 d, mortality actually increased in treated versus untreated cystic mice (33).…”
Section: Discussionmentioning
confidence: 93%
“…The timing of overexpression during the course of development may also impact the effect of growth factor on disease progression. In the bpk mouse, administration of exogenous EGF before 9 d of age improved renal function but not cystic kidney appearance, whereas, when treatment was continued beyond 9 d, mortality actually increased in treated versus untreated cystic mice (33).…”
Section: Discussionmentioning
confidence: 93%
“…These results may also reflect the pleiomorphic effects that EGF signaling and its inhibition may have in different model systems. Previous studies have shown that the role of EGF in cystogenesis may depend on the stage of the development [50], and that administration of EGF during the neonatal period (days 1 to 9, a period critical for the differentiation of the collecting duct) retarded the development of azotemia, common bile duct dilation, and intrahepatic bile duct proliferation in the bpk mouse [50] and renal cystogenesis and azotemia in the cpk mouse [51].…”
Section: Discussionmentioning
confidence: 98%
“…Transgenic mice that overexpress TGF-␣ develop renal cystic disease, and renal expression of a TGF-␣ transgene accelerates PKD progression in pcy mice (36,72). However, the impact of the mislocalized EGF-TGF-␣-EGFR axis appears to be developmentally regulated, as EGF treatment in neonatal mice actually attenuates PKD progression (37,91).…”
Section: Erbb Receptors and Tyrosine Kinase Inhibitorsmentioning
confidence: 99%